Revisiting Delithiated Li1.2Mn0.54Ni0.13Co0.13O2: Structural Analysis and Cathode Properties in Magnesium Rechargeable Battery Applications - Naoya ISHIDA; Ryuta NISHIGAMI; Masaki MATSUI; Toshihiko MANDAI; Kiyoshi KANAMURA; Naoto KITAMURA; Yasushi IDEMOTO (Electrochemistry, 2021)
Chemically-delithiated Li1.2Mn0.54Ni0.13Co0.13O2 is regarded as a potential candidate of cathode active materials for magnesium rechargeable batteries owing to its large deliverable capacity and high operation voltage compared to conventional layered transition metal oxides. Our previous study suggested its chemical composition as Li0.13Mn0.54Ni0.13Co0.13O2−δ by X-ray diffraction combined with XAFS analysis. We herein re-analyzed the substantial composition and crystal structure by employing titration technique and combination of neutron and synchrotron X-ray diffractions. Two topotactic phases both belonging to the space group of R3m were strongly suggested by Rietveld analysis, and the chemical formula was subsequently re-defined as Li0.17Mn0.72Ni0.18Co0.18O2 where oxygen defects were filled by a rearrangement from C2/m structure. Although the battery performance of that active material was poor in the previous study, the discharge capacity greater than 400 mAh g−1, ca. 95 % of the theoretical capacity, was achieved by using certain anodically stable electrolytes and specific cell configuration. This result strongly implies that the R3m structure is particularly suitable as a host material for Mg2+ intercalation.